(untitled) (Research, Society and Development, 2024)
Rare diseases (RDs) are life-threatening conditions affecting 263 to 446 million people globally. However, diagnosing these diseases often takes years, leading to a "diagnostic odyssey." The impact of these delays is often underreported, leaving patients’ consequences unclear. This protocol intends to guide a scoping review about the current knowledge on RDs, identify gaps and clarify reasons for diagnostic delays, focusing on global trends and Brazil. Following PRISMA-ScR guidelines and using the Joanna Briggs Institute’s framework, searches will be conducted in five databases (PubMed, LILACS, Embase, Cochrane Library, and IBECS) and grey literature from reputable sources. Two authors will independently screen and extract data, resolving discrepancies with a third reviewer. Data will be analyzed qualitatively and presented through figures and narrative synthesis, with statistical analysis applied when pertinent. This protocol will supply a step-by-step guide for a scoping review that is going to provide critical insights into the effects of diagnostic delays in rare diseases, offering valuable information to improve diagnostic process and patient care. This protocol has been registered in the Open Science Framework (https://osf.io/zte3c/?view_only=90c5abadfbb646d6a64bc284314e696c).